$\fraction{u + 2}{u - 4} - 1 = \fraction{u + 1}{u - 3}$

共享

\left(u-3\right)\left(u+2\right)+\left(u-4\right)\left(u-3\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6+\left(u-4\right)\left(u-3\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6+\left(u^{2}-7u+12\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6-u^{2}+7u-12=\left(u-4\right)\left(u+1\right)

-u-6+7u-12=\left(u-4\right)\left(u+1\right)

6u-6-12=\left(u-4\right)\left(u+1\right)

6u-18=\left(u-4\right)\left(u+1\right)

6u-18=u^{2}-3u-4

6u-18-u^{2}=-3u-4

6u-18-u^{2}+3u=-4

9u-18-u^{2}=-4

9u-18-u^{2}+4=0

9u-14-u^{2}=0

-u^{2}+9u-14=0

u=\frac{-9±\sqrt{9^{2}-4\left(-1\right)\left(-14\right)}}{2\left(-1\right)}

u=\frac{-9±\sqrt{81-4\left(-1\right)\left(-14\right)}}{2\left(-1\right)}

u=\frac{-9±\sqrt{81+4\left(-14\right)}}{2\left(-1\right)}
-4 乘上 -1。
u=\frac{-9±\sqrt{81-56}}{2\left(-1\right)}
4 乘上 -14。
u=\frac{-9±\sqrt{25}}{2\left(-1\right)}

u=\frac{-9±5}{2\left(-1\right)}

u=\frac{-9±5}{-2}
2 乘上 -1。
u=-\frac{4}{-2}

u=2
-4 除以 -2。
u=-\frac{14}{-2}

u=7
-14 除以 -2。
u=2 u=7

\left(u-3\right)\left(u+2\right)+\left(u-4\right)\left(u-3\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6+\left(u-4\right)\left(u-3\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6+\left(u^{2}-7u+12\right)\left(-1\right)=\left(u-4\right)\left(u+1\right)

u^{2}-u-6-u^{2}+7u-12=\left(u-4\right)\left(u+1\right)

-u-6+7u-12=\left(u-4\right)\left(u+1\right)

6u-6-12=\left(u-4\right)\left(u+1\right)

6u-18=\left(u-4\right)\left(u+1\right)

6u-18=u^{2}-3u-4

6u-18-u^{2}=-3u-4

6u-18-u^{2}+3u=-4

9u-18-u^{2}=-4

9u-u^{2}=-4+18

9u-u^{2}=14

-u^{2}+9u=14

\frac{-u^{2}+9u}{-1}=\frac{14}{-1}

u^{2}+\frac{9}{-1}u=\frac{14}{-1}

u^{2}-9u=\frac{14}{-1}
9 除以 -1。
u^{2}-9u=-14
14 除以 -1。
u^{2}-9u+\left(-\frac{9}{2}\right)^{2}=-14+\left(-\frac{9}{2}\right)^{2}

u^{2}-9u+\frac{81}{4}=-14+\frac{81}{4}
-\frac{9}{2} 的平方是將分式的分子和分母兩個都平方。
u^{2}-9u+\frac{81}{4}=\frac{25}{4}

\left(u-\frac{9}{2}\right)^{2}=\frac{25}{4}

\sqrt{\left(u-\frac{9}{2}\right)^{2}}=\sqrt{\frac{25}{4}}

u-\frac{9}{2}=\frac{5}{2} u-\frac{9}{2}=-\frac{5}{2}

u=7 u=2